How to design and evaluate a direct marketing test - Hathway, Nigel (Henry Stewart Talks, 2008)
Importance of testing, What to test?, Statistical concepts, How large a sample size?, Example, Selecting the sample, Formula for sample size, Practical considerations, Practical example: incentive test, Practical example: creative test